Supercritical Fluid fractionation of mentha suaveolens: concentration of functional properties - Mainar, Ana María; Rota, Carlota Giménez; González-Coloma, A.; Urieta, J.S.; Lorán, S.; Rota, M.C. (Jornada de Jóvenes Investigadores del I3A, 2018)
Supercritial Antisolvent Fractionation process was optimiced for the concentration of Mentha suaveolens bioactives in two different fractions. Their composition was analysed with HPLC. The antimicrobial activity of these fractions was assayed. The SAF process fractionated M. suaveolens tincture in two enriched fractions in different bioactives concentrating those with antimicrobial activity in one of them.